Human bone tissue-derived ECM hydrogels: Controlling physicochemical, biochemical, and biological properties through processing parameters - Yang-Hee Kim; Gianluca Cidonio; Janos M. Kanczler; Richard OC. Oreffo; Jonathan I. Dawson (Bioactive Materials)
Decellularized tissues offer significant potential as biological materials for tissue regeneration given their ability to preserve the complex compositions and architecture of the native extracellular matrix (ECM). However, the evaluation and derivation of decellularized matrices from human bone tissue remains largely unexplored. We examined how the physiochemical and biological properties of ECM hydrogels derived from human bone ECM could be controlled by manipulating bone powder size (45–250 μm, 250–1000 μm, and 1000–2000 μm) and ECM composition through modulation of enzyme digestion time (3-5-7 days).A reduction in material bone powder size and an increase in ECM digestion time produced enhanced protein concentrations in the ECM hydrogels, accompanied by the presence of a diverse array of proteins and improved gelation strength. Human bone marrow-derived stromal cells (HBMSCs) cultured on ECM hydrogels from 45 to 250 μm bone powder, over 7 days, demonstrated enhanced osteogenic differentiation compared to hydrogels derived from larger bone powders and collagen gels confirming the potential of the hydrogels as biologically active materials for bone regeneration. Digestion time and bone powder size modulation enabled the generation of hydrogels with enhanced release of ECM proteins and appropriate gelation and rheological properties, offering new opportunities for application in bone repair.